Eric Landowski. Short Semiotic Manifest in Honour and for Attention of Comrade Sociologist Pekka Sulkuneni. Transl. by Kęstutis Nastopka - Landowski , Eric (Semiotika, 2019)
Iš prancūzų k. vertė Kęstutis Nastopka. Versta iš: Landowski, Eric. Petit manifeste sémiotique en l’honneur et à l’attention du camarade sociologue Pekka Sulkunen. Actes Sémiotiques, 2017, Nr. 120 (http://epublications.unilim.fr/revues/as/5816)